Retórica e memória: estratégias persuasivas no discurso epistolar - Ribeiro, Luisiana Ferreira Moura (2020)
Old and modern studies about Rhetoric has a little focus on the theme of memory, and when they do so, they particularly emphasize mnemonic art and its importance for discourse communication. We understand, however, that memory and its processes are inherent in human practices and closely linked to the development and the course of man over time. Due to this area to be explored, with regard to Rhetoric, this research has as its theme epistolary rhetoric and the implication of memory as a repository of arguments and strategies for the construction of this type of discourse. The problem, therefore, is to question the extent to which memory provides the basis for the argumentation in the space-time mismatch in the letters exchanged between Mário de Andrade and Carlos Drummond de Andrade during the 1920s. For this, the rhetorical references are based on Aristotle (2005 [384-322 BC]), Reboul (2004), Meyer (2007), Tringali (2014) and Perelman and Olbrechts-Tyteca (2014), with contributions from Ferreira, L. A. (2010). The general objective is to examine the strategies of selection and disposition of arguments by means, respectively, of invention and disposition, steps of the rhetorical system. As specific objectives, we chose: to verify how the speaker rescues and articulates the arguments concerning social memory to re-hierarchize the values of the audience and to persuade; To identify to what extent the audience is persuaded and corroborates the effectiveness or not of the motivating speech of epistolary response. The theoretical basis of structure, tensions, and transformations of epistolary discourse considers Victor (1980 [4th century AD]), Foucault (1992) and Bazerman (2011). The studies on memory and cognition by Van Dijk (2008), and memory, individual and society in Pollak (1992), Bosi (1993), Le Goff (2013) and Gondar (2016) provide the concepts of memory. The results indicate that memory is a repository of arguments and strategies that has rhetorical potential because of its strength to arouse passions and, therefore, move values towards a rhetorical goal. Also, due to its inalienable condition for action and human development, it is stands up as a necessary resource to every rhetorical course, from the construction to the reception of the discourse, through memory models constructed and continuously reformulated from man's experiences and interactions; therefore, it surpasses the mnemonic function. Moreover, we find from the application of the first two stages of the rhetorical system that the tessitura of the discourse of the two speakers reveals wit in the selection and strategy in the disposition of the arguments in such a way that it is effective in convincing and persuading